Composition physico-chimique du lait de chèvre de l'Est de l'Ukraine - Shapovalov, Sergey; Шаповалов, Сергій; Fotina, Tatiana; Фотіна, Тетяна; Kalachnikov, Vyacheslav; Калашніков, В'ячеслав; Zazharska, Nadia; Зажарська, Надія Миколаївна (Université Ibn Khaldoun – Tiaret, Algérie, 2015)
This paper presents the results of monitoring indicators of quality goat milk in the eastern region of Ukraine. Determination of milk quality of 110 dairy goats in Sumy, Kharkov and Donetsk regions of Ukraine was conducted. The experimental part of the study consisted research on 15 lactating goats. The study was conducted at the Institute of Animal test center NAAS of Ukraine, which is accredited by the requirements of Ukraine Standard ISO/IEC 17025: 2006. Reference physical, technological and chemical parameters of milk goats were established. It can be used in breeding schemes aimed at improving the quality of goat milk. Established conversion factors of milk indicators (casein fractions on the mass fraction of total protein) can be used by milk processors at the cheese production. As a result of experimental studies established the freezing point of goat milk in the Eastern region of Ukraine, which is minus 0.557 °C, which can be used to identify fraud goat milk with water.Cet article présente les résultats de surveillance des indicateurs de lait de chèvre dans la région orientale de l'Ukraine. Nous avons déterminé la qualité du lait 110 chèvres laitières à Soumy, Kharkiv et Donetsk régions en Ukraine. La partie expérimentale de l'étude comprenait 15 chèvres en lactation. L'étude a été menée au centre d'essai Institut de animaux de l'Académie nationale des sciences agricoles de l'Ukraine, qui est accrédité par les exigences de Standard de l'Ukraine ISO/IEC 17025: 2006. Référence établi paramètres physiques, chimiques et technologiques de chèvres de lait qui peuvent être utilisés dans les programmes de sélection visant à améliorer la qualité du lait. Les facteurs de conversion des indicateurs établis de lait (fractions de caséine sur la fraction de masse des protéines totales) peuvent être utilisés dans transformation du lait. En conséquence d'études expérimentales établi le point de chèvres laitières de congélation dans la région de l'Est de l'Ukraine, qui est moins 0,557 °C, qui peut être utilisé pour identifier les chèvres de fraude lait avec de l'eau.У статті подано результати моніторингу показників козиного молока у східному регіоні України. Визначено якість молока 110 молочних кіз у Сумській, Харківській та Донецькій областях України. Експериментальна частина дослідження включала 15 дійних кіз. Дослідження було проведено в випробувальному центрі Інституту тваринництва НААН України (м. Харків), який акредитований за вимогами ДСТУ ISO/IEC 17025:2006. Встановлені референтні значення фізичних, технологічних, хімічних показників козиного молока, які можуть бути використані в програмах розведення для підвищення якості молока. Встановлені коефіцієнти перерахунку показників молока (щодо фракцій казеїну) від масової частки загального протеїну можуть використовуватися переробниками за умов використання молока кіз у сироварінні. В результаті експериментальних досліджень встановлено температуру замерзання молока кіз у східному регіоні України, яка становить мінус 0,557 ° С, що може бути використана для ідентифікації фальсифікації козиного молока водою.
Фізико-хімічний склад козиного молока східної України.
Physico-chemica composition of goat milk from eastern Ukraine
Keywords: lait de chèvre; козине молоко; goat milk; composition chimique; хімічний склад; chemical composition; caséine; казеїн; casein; point de congélation; точка замерзання; freezing point